A Normative Baseline for the Srs-22 From Over 1000 Healthy Adolescents in India: Which Demographic Factors Affect Outcome?. Issue 13 (1st July 2017) - Verma, Kushagra; Nathan, Senthil T.; Comer, Carly D.; Lonner, Baron; Shah, Suken A.
Abstract : Study Design: A prospective analysis. Objective: This study aims to 1) establish a baseline for the SRS-22 in South East Asia and 2) evaluate the influence of patient demographics on the SRS-22. Summary of Background Data: Previous studies have established a baseline for the SRS-22 in the US and described the impact of patient demographics. While the SRS-22 is used internationally, limited normative data are available. Methods: After approval from the local hospital and school board, 1200 adolescents (age 10–18 years) were asked to anonymously complete the SRS-22 in English. The following demographic factors were assessed: height, weight, age, gender, household income (range <30K to >200K), and household status (single/dual parent income). Participants with a prior spine history or active medical problems were excluded. Statistical analysis was done with a Pearson correlation followed by an analysis of variance (ANOVA). Results: One thousand nineteen unaffected adolescents completed the SRS-22 (mean age 14.4 ± 1.6 years). Demographics were as follows: gender (42%F, 58%M), household status (640 single/379 dual), height (157 ± 12 cm), weight (46 ± 11.2 kg), body mass index (BMI; 18.5 ± 3.6). SRS-22 score for all patients and by gender: Mean [4.0 ± 0.4, (F)4.0 ± 0.4, (M)3.9 ± 0.4, P < 0.0001], Activity [3.9 ± 0.4, (F)4.0 ± 0.5, (M)3.9 ± 0.6], Pain [4.3 ± 0.6; (F)4.4 ± 0.6, (M)4.2 ± 0.7, P < 0.001], Image [3.9 ± 0.6, (F)3.9 ± 0.6, (M)3.9 ± 0.6], and Mental [3.7 ± 0.6, (F)3.8 ± 0.6, (M)3.7 ± 0.6, P < 0.001]. Male gender was associated with worse pain (-0.15), mental health (-0.11), and overall SRS-22 score (−0.11). Age was correlated with a worse image ( r = −0.17, P = < 0.000), while higher BMI was associated with less pain (0.07/0.02). Conclusion: Younger age, female gender, and higher BMI correlated with a better SRS-22 score. Income and household status did not affect SRS-22. These findings contrast data gathered in the US but should be considered in conjunction with the minimal clinically important difference (MCID). This study establishes the first normative baseline for the SRS-22 in SE Asia and analyzed the effect of demographics on the outcome score. Level of Evidence: 2